(untitled) (Research, Society and Development, 2022)
“Helicobacter pylori” is a bacterium located in the stomach and is resistant to acidic sites, providing enough energy for its survival. Being one of the most common causes of gastroduodenal diseases, the bacterium is responsible for a high percentage of gastritis, gastric reflux, gastric ulcers and gastroenteritis. The objective of this study was to inform health professionals about the attention and care in the treatment of patients with Helicobacter Pylori, presenting what the bacterium is, forms of exams to obtain the diagnosis and treatment. The research will be carried out through bibliographic reviews of materials found in scientific databases, with a descriptive study, analyzing detailed data to solve the problem and hypotheses under study. The information will be collected by the documentary method through articles of a qualitative nature. However, the studies highlighted that the patient may experience some reactions in cases of peptic ulcers or gastritis caused by contamination of the bacteria. The treatment to eradicate the bacteria is classified as first line that lasts for 14 days. Second-line therapy is performed for 10 to 14 days, and clarithromycin may be substituted for levofloxacin.